Examining 'Space' in peer-to-peer accommodation settings - Farmaki, Anna; Christou, Prokopis A. (My University, 2019)
By offering visitors the opportunity of an alternative accommodation experience, Peer-to- Peer (P2P) accommodation has contributed to the popularity of commercialised homes as a more authentic accommodation setting. Surprisingly, the concept of 'space' within P2P accommodation has received minimal academic attention. Utilising Lefebvre's (1974) theory of the production of space and Foucault's (1986) notion of heterotopias, this research note aims to advance understanding on how space is reproduced and interpreted within P2P accommodation; thereby, influencing the practice of both P2P accommodation hosts and guests. Drawing from Airbnb host and guest perceptions and experiences, we offer insights on how a private space is formed and reproduced to serve commercial purposes through a process of continuous negotiation whereby physical, social and symbolic spatial dimensions are attributed and arranged to inform the sharing practice between hosts and guests.
Keywords: Airbnb; Guests; Hosts; Peer-to-peer accommodation; Space